Pernikahan Usia Dini dan Dampak Perceraian di Pedesaan - Yelia Ahya Robby; Ela Siti Fauziah (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2021)
Early marriage is an ancient issue that was covered by a pile of historical sheets. Weddings are done at an early age may end up with a divorce in the age of marriage that is still very young as well. Marriage at an early age where a person is not ready either mentally or physically, often creates problems, later on, not even a bit of a mess in the middle of the road, and eventually ends up with a divorce. Cases of marriage minors who then ended up with divorce to date are still many in the encounter in Indonesia, both in remote villages and in areas that have grown even in big cities. From here the author is interested to examine the phenomenon of early marriage in the Village Ciodolog Cidolog District Ciamis.